A randomized controlled trial of antibody response to 2018–19 cell-based vs. egg-based quadrivalent inactivated influenza vaccine in children. Issue 33 (14th July 2020) - Moehling, Krissy K.; Zimmerman, Richard K.; Nowalk, Mary Patricia; Jeng Lin, Chyongchiou; Martin, Judith M.; Alcorn, John F.; Susick, Michael; Burroughs, Ashley; Holiday, Crystal; Flannery, Brendan; Levine, Min Z.
Highlights: Cell-based influenza vaccines may offer better protection than egg-based vaccines. An RCT compared immune response of children to egg- and cell-based influenza vaccine. High baseline titers precluded seroconversion for most enrollees; no difference by vaccine type. Previous year vaccinees vs. unvaccinated had lower GMTs for some virus strains. Abstract: Background: Current influenza vaccine effectiveness (VE) improvement efforts focus on minimizing egg adaptation mutations during manufacture. This study compared immune response of two FDA-approved quadrivalent inactivated influenza vaccines in an unblinded randomized controlled trial. Methods: Participants were 144 community dwelling, healthy children/adolescents aged 4–20 years, randomized 1:1 in blocks of 4 to a vaccine grown in cell culture (ccIIV4 [Flucelvax®]; n = 85); or in egg medium (IIV4 [Fluzone ®]; n = 83). Blood was drawn at day 0 prevaccination and at day 28 (19–35 days) post vaccination. Hemagglutination inhibition (HI) assays against A/H1N1 and both B strains and microneutralization (MN) assays against egg-based and cell-based A/H3N2 strains were conducted. The primary outcome measure was seroconversion (day 28/day 0 titer ratio ≥ 4 with day 28 titer ≥ 40). Secondary outcomes were elevated titers (day 28 HI titer ≥ 1:110), geometric mean titers (GMTs) and mean fold rise (MFR) in titers. Outcomes were compared for 74 ccIIV4 recipients and 70 IIV4 recipients, and for those vaccinated and unvaccinated the previous year. Only the HI and MN laboratory analysis team was blinded to group assignment. Results: In this racially diverse (81% non-white) group of children with a median age of 14 years, baseline demographics did not differ between vaccine groups. At day 0, half or more in each vaccine group had elevated HI or MN titers. Low seroconversion rates (14%-35%) were found; they did not differ between groups. Among 2018–19 ccIIV4 recipients, those unvaccinated in the previous season showed significantly higher MFR against A/H1N1 and A/H3N2 cell-grown virus than the previously vaccinated. Similar results were found for MFR against B/Victoria among 2018–2019 IIV4 recipients. Conclusion: In mostly older children with high baseline titers, no differences in seroconversion or other measures of antibody titers were found between ccIIV4 and IIV4 recipients against egg- and cell-grown influenza vaccine viruses. Clinical Trials No: NCT03614975.